Influence of interleukin 1α on superoxide anion, platelet activating factor release and phospholipase A(2) activity of naive and sensitized guinea-pig alveolar macrophages - Mugnai, Sabrina (1997)
1. We studied the effect exerted by hr-interleukin-1α (IL-1α) on responsiveness of alveolar macrophages (AM) from naive and sensitized guinea-pigs, through O(2)‐˙ production (by ferricytochrome C reduction), platelet-activating factor (PAF) release (by platelet aggregation), prostaglandin E(2) (PGE(2)) release (by a radioimmunoassay), and cytosolic phospholipase A(2) (cPLA(2)) activity (by hydrolysis of radioactive substrate). 2. In naive guinea-pig AM, 0.06 nM hr-IL-1α pretreatment decreased by 65% O(2)‐˙ release stimulated with 10 nM fMLP. In contrast, O(2)‐˙ production was not affected in sensitized guinea-pig AM. 3. O(2)‐˙ release elicited by fMLP stimulation in both cell groups was affected by PLA(2) inhibitors (10 μM bromophenacyl bromide, BPB or 10 μM methylprednisolone, MP). In contrast, 10 μM arachidonyl trifluoromethyl ketone (AACOCF(3)), a cPLA(2) inhibitor, was ineffective. 4. In naive AM, PAF release was elicited by hr-IL-1α pretreatment and by separate fMLP-stimulation, but when the stimulus was added to hr-IL-1α-pretreated cells inhibition of PAF release was observed. In sensitized AM, PAF release was lower than that found in naive guinea-pig AM in both hr-IL-1α-pretreated and fMLP-stimulated cells. 5. PGE(2) release was unaffected by hr-IL-1α pretreatment and it was decreased by fMLP in both naive and sensitized AMs. The latter released less PGE(2) than naive cells in basal conditions and after fMLP treatment. 6. Sensitized AM showed a greater cPLA(2) activity in all experimental conditions in comparison to naive cells. cPLA(2) activity assayed in the cytosolic fraction was found to be enhanced by hr-IL-1α pretreatment and by fMLP stimulation in naive but not in sensitized AM. However, when the stimulus was added to hr-IL-1α-pretreated cells we observed a decrease in cPLA(2) activity in the cytosol and an increase in the membranes, thus suggesting a translocation of enzymatic activity. 7. In conclusion, hr-IL-1α can modulate the responsiveness of AM from naive and sensitized guinea-pigs, as suggested by changes found in the release of PAF and O(2)‐˙. and in cPLA(2) activity; therefore, sensitization itself may affect cellular responsiveness.